2022
DOI: 10.3390/ijms23052689
|View full text |Cite
|
Sign up to set email alerts
|

Pediococcus acidilactici CECT9879 (pA1c) Counteracts the Effect of a High-Glucose Exposure in C. elegans by Affecting the Insulin Signaling Pathway (IIS)

Abstract: The increasing prevalence of metabolic syndrome-related diseases, including type-2 diabetes and obesity, makes it urgent to develop new alternative therapies, such as probiotics. In this study, we have used Caenorhabditis elegans under a high-glucose condition as a model to examine the potential probiotic activities of Pediococcus acidilactici CECT9879 (pA1c). The supplementation with pA1c reduced C. elegans fat accumulation in a nematode growth medium (NGM) and in a high-glucose (10 mM) NGM medium. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“…Furthermore, some specific bacterial species are associated with a lower level of insulin resistance in the context of obesity. In a nematode, the supplementation with Pediococcus acidilactici neutralized the effect of high glucose levels, apparently by modulation of the insulin/IGF-1 signaling pathway (51). Similarly, in obese and lean Asian subjects, a negative correlation has been found between the intestinal abundance of Akkermansia muciniphila and the risk of increased severity of insulin resistance (52).…”
Section: Microbiota and Pathologies Associated With Obesitymentioning
confidence: 98%
“…Furthermore, some specific bacterial species are associated with a lower level of insulin resistance in the context of obesity. In a nematode, the supplementation with Pediococcus acidilactici neutralized the effect of high glucose levels, apparently by modulation of the insulin/IGF-1 signaling pathway (51). Similarly, in obese and lean Asian subjects, a negative correlation has been found between the intestinal abundance of Akkermansia muciniphila and the risk of increased severity of insulin resistance (52).…”
Section: Microbiota and Pathologies Associated With Obesitymentioning
confidence: 98%
“…54 Hence, these findings support the anti-lipogenic role of pA1c® in the liver of individuals with obesity and are in agreement with previous studies conducted by our group on C. elegans and mice. 23,55…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, this rise in beta-oxidation, together with the overexpression of the glucose metabolism genes Slc2a1 and Slc2a4, is in concordance with our previous studies on C. elegans and mice, where we demonstrated that the mechanism of action of pA1c® affected the insulin signalling and beta-oxidation pathways. 23,55 Looking more closely at Fig. 2B reveals a downregulation of perilipin-1 (Plin-1), which is a gene that encodes lipid droplet surface proteins named perilipins, in the pA1c® rats compared with the HFS rats.…”
Section: Food and Function Papermentioning
confidence: 99%
See 1 more Smart Citation
“…An enhanced ROS production can inhibit insulin signaling and then activated daf-16 stimulates the expression of fat-5 , ultimately leading to an excessive fat accumulation [ 101 ]. The gene expression analysis demonstrated that Pediococcus acidilactici CECT9879 (pA1c) could alleviate the metabolic syndrome by reversing the glucose-nuclear-localization of daf-16 , overexpressing ins-6 , daf-2 , or ageing alteration-1 ( age-1 ), and downregulating the key genes for the biosynthesis of FAs [ 102 ]. Xiong et al found that Fuzhuan Tea relied on the regulation of the expression of fat-7 by DAF-16/FoxO to reduce the adiposity in C. elegans on glucose-rich diets [ 103 ].…”
Section: Conserved Fat Metabolism Signaling Pathways In C E...mentioning
confidence: 99%